Fruit quality of yellow passion fruit fertilized with nitrogen and humic substances - Silva, Roberto Lustosa; Lucena Cavalcante, Ítalo Herbert; Melo de Sousa, Karla dos Santos; Galhardo, Cristiane Xavier; Santana, Elisson Alves; Lima, Deisiele Diniz (Comunicata Scientiae, 2015)
The quality of yellow passion fruits is affected by genetic and exogenous factors like climate, soil and agricultural practices such as fertilizing and irrigation. Thus, an experiment was developed from February to December 2013 to evaluate the effect of nitrogen fertigation and humic substances on physical and chemical quality of yellow passion fruits. The experimental design used was in complete blocks design with subdivided plots with N rates (180, 200, 260, 330 and 350 kg ha-1 year-1) in parcels and application of humic substances (with and without) in sub-parcels, with five repetitions of six plants. At 210 days after transplanting all fruits were harvested and conducted to the laboratory for evaluation of fruit mass, longitudinal and transversal fruit diameter, skin thickness, pulp percentage, pulp pH, vitamin C, soluble solids, titratable acidity, and soluble solids/titratable acidity ratio. Fruits produced, independently of the treatment, are adequate for consumption as in natura or processed fruit. It is possible to recommend a dose of 260 kg ha-1 of N without humic substances for production of good quality yellow passion fruits.